Comparative analysis of using atezolizumab vs. durvalumab in combination with platinum-containing chemotherapy in adult patients with advanced small cell lung cancer - I. S. Krysanov; E. V. Makarova; V. Yu. Ermakova (Фармакоэкономика)
Background. In recent decades, a course of chemotherapy with etoposide (EP) and platinum preparations (сarboplatinum, CP) has been recommended as a standard first-line treatment option in patients with advanced small cell lung cancer (SCLC), but with the advent of new immunological drugs, immune checkpoint inhibitors, approaches to therapy have changed. Based on randomized clinical trials, courses combining traditional platinum-containing chemotherapy with inhibitors of programmed death-ligand 1 (PD-L1) atezolizumab (ATZ) or durvalumab (Durv) have been included in many clinical recommendations for oncologists.Objective: to evaluate the clinical and cost-effectiveness of using ATZ and Durv as first-line therapy in advanced SCLC adult patients within the Russian healthcare system.Material and methods. The model of treatment of advanced SCLC adult patients in conditions of the healthcare system of the Russian Federation included the most popular options for first-line immunochemotherapy: CP/EP + ATZ and CP/EP + Durv courses. Pharmacoeconomic cost-effectiveness analysis, sensitivity analysis of the selected model to changes in its initial parameters, budget impact analysis were carried out.Results. The total medical costs for CP/EP + ATZ course (2,310,546.07 rubles) were significantly lower than for the CP/EP + Durv course (4,081,833.98 rubles). With comparable costs for the treatment of complications (426,175.17 and 407,704.50 rubles, respectively), the cost of Durv exceeded ATZ by 94.8%. When conducting a cost-effectiveness analysis, the advantage was retained by the CP/EP + ATZ course, the cost-effectiveness ratios for which amounted to 187,849.27 rubles per month of patient's life and 444,335.78 rubles per month of patient's life without progression (for CP/EP + Durv, 316,421.24 and 800,359.60 rubles, respectively). When choosing the CP/ET + ATZ strategy, the savings will be 128,571.96 rubles per month of life and 356,023.82 rubles per month of life without progression. Sensitivity analysis demonstrated the stability of the developed model: to increase in the price of the CP/EP + ATZ course up to +68%; to decrease in overall survival with the course of CP/EP + ATZ up to –40%; to decrease in progression-free survival with the course of CP/EP + ATZ to –44%. Budget impact analysis showed that with a possible cohort size of 4,448 people an increase in the proportion of patients receiving CP/EP + ATZ course from 70% to 90% will reduce budget costs by 1,575,737,725.38 rubles per year, which will allow additional treatment of 681.9 advanced SCLC patients per year (+15.3%).Conclusion. The use of ATZ combined with standard platinum-containing chemotherapy in advanced SCLC adult patients as the first-line therapy is clinically and cost-effective strategy within the Russian healthcare system, as it allows to reduce therapy costs compared to Durv and treat more SCLC patients, which fully corresponds to the target indicators of the federal program “Oncology”.